Enriching the teaching of social studies in the elementary grades with music - Alcaraz, Naomi Gapuzan (1977)
The study presented a treasure-house of 80 songs depicting Social Studies concepts, related ideas and generalizations based from the UP NSDB Scope and Sequence Guide and from the Junior Citizens' Magazine, Social Studies Publications, Incorporation. These compiled songs were analyzed, classified and sorted out in terms of concepts they represent and the grade level they belong to. Lesson plans using the conceptual approach were made to serve as an eye opener for developmental purposes or for culminating activities.